ASSESSMENT OF THE USE OF ANTI-CRISIS MANAGEMENT TOOL JSC «PRIVATBANK» - Малафєєв, Тимур; Жигунов, Олексій (Socio-economic relations in the digital society, 2019)
The article states that the current state of the banking sector of Ukraine requires banking activity to focus on anti-crisis management, with the help of which it is possible to timely determine and solve problems successfully. It is noted that banks have signifi cant problems related to the management of their problem assets. Anti-crisis management is an integral part of banking management and should be carried out on a permanent basis. Given that the open stage of the crisis occurs with a coincidence of a number of factors and reasons that have been suffi ciently developed, it is very important to be prepared to identify problems in a timely manner and to take appropriate measures in a timely manner in order to prevent bankruptcy. The article examines the impact of individual anti-crisis instruments on improving the fi nancial condition of the bank, for example, JSC CB «PrivatBank». It was clarifi ed that the financial status of JSC «PrivatBank» bank is assessed as unstable, that is, its fi nancial stability is insuffi ciently provided by the capital, which can protect the bank from possible risky losses in its activities. At the same time, the bank is capable of fulfilling its obligations to potential customers in a timely manner and in full, as well as providing stability to the market of banking products. Anticrisis strategy will accelerate and simplify the adoption of the required managerial decisions and reduce possible alternative actions. Banking institutions should constantly improve the methodical component of the crisis strategy, especially as regards the addition of qualitative indicators of liquidity, since it is the liquidity crisis that affects the further functioning of the bank. For example, the qualitative indicators can include a change in the credit rating (domestic or foreign) that is assigned to a banking institution.